A centennial refurbishment of Dunlop's emporium of contractual concepts: Cavendish Square Holding BV v Talal El Makdessi and ParkingEye Limited v Beavis [2015] UKSC 67. (June 2016) - Swaminathan, Shivprasad
Since Dunlop Pneumatic Tyre Co v New Garage Motors (1915), the law pertaining to the enforceability of stipulated contractual sums in most of the common law world has revolved around the dichotomy between unenforceable penalties that are in terrorem on the one hand and enforceable liquidated damages that are genuine pre-estimates of loss, on the other. The United Kingdom Supreme Court took up the Dunlop test for reconsideration in Cavendish Square Holding BV v Talal El Makdessi and ParkingEye Limited v Beavis (2015). While on the surface the court 'upheld' the penalties rule in Dunlop, in quintessentially common law fashion, it recast it in such a manner that the old rule survives only in name. It renders otiose the enquiry into whether any stipulation is a genuine pre-estimate and hence a liquidated damages clause and redefines a penalty as a stipulation that is unconscionable in relation to the 'interest' protected, whether or not in terrorem . Practically, the new test operates as a test of 'reasonableness' of stipulated sums would. Theoretically, however, the new test continues to rest on a questionable distinction between primary and secondary obligations.